Integrasi Pendidikan Lingkungan dalam Pembelajaran Biologi Sekolah Menengah: Sebuah Kajian Literatur Menuju Kesadaran Ekologis Siswa - Supratman, Supratman; Suhirman, Suhirman; Rusdianto, Rusdianto; Alhafizin, M. (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the integration of environmental education into Biology learning and its contribution to enhancing students' ecological consciousness. This research employed a literature review method by analyzing 35 scientific articles published between 2019 and 2024 from accredited national journals and reputable international journals. The findings indicate that integrating environmental education through strategies such as project-based learning, the use of local ecosystems as learning resources, and the reinforcement of ecological values in Biology content can significantly improve students’ environmental literacy, conservation attitudes, and participation in real environmental actions. In addition, the integration of disaster risk reduction education into Biology lessons is essential in equipping students with adaptive skills to face increasing natural hazards. However, challenges such as limited teacher competence, insufficient resources, and lack of institutional support remain significant obstacles. Therefore, strengthening teacher capacity and developing contextual environment- and disaster-based teaching materials are key recommendations. This review confirms that integrating environmental and disaster education into Biology instruction is a strategic approach to fostering ecologically aware, resilient, and responsible learners.